Effects of sensory stimulation on balance and postural control in diabetic neuropathy: systematic review - Giri, Hetal S.; Borkar, Pradeep (International Journal of Research in Medical Sciences, 2021)
Diabetic peripheral neuropathy is a complication of Diabetes Mellitus and is the most common noncommunicable disease. It involves decreases in the sensations and Lower extremity strength leading to reduce dynamic stability in balance and postural control. The purpose of the study is to review the effects of sensory stimulation interventions on Balance and Postural control in Diabetic peripheral neuropathy. A systematic review was conducted following the centers for Goggle scholar, PUBMED and science direct database using the keywords Sensory Stimulation, Balance, Postural control, Diabetic neuropathy. The time frame of the search was from 2006 to 2021. The review resulted in search of 18 articles with duration from 1 day to 26 weeks with a total population of 1,422 diabetes Mellitus type I and type II patients from the year 2006 to 2021. There were strong evidences of effects of sensory stimulation on postural control and Balance with noticeable difference in DPN. Based on our analysis results, most of the study stated that Vibration, Plantar Massages, Kinesiotaping, Rocker shoe, Vibromedical insole, Conventional exercises with proprioception stimulation, Mechanical noise have shown significant difference on balance and postural control. Whereas, offloading devices did not show any remarkable variance. The currently existing studies require a clear recommendation on whether which intervention is more effective. Thus, longer duration studies are required to improve balance and postural control in Diabetic Neuropathy.